2018 IEEE Winter Conference on Applications of Computer Vision (WACV) 2018
DOI: 10.1109/wacv.2018.00009
|View full text |Cite
|
Sign up to set email alerts
|

To Frontalize or Not to Frontalize: Do We Really Need Elaborate Pre-processing to Improve Face Recognition?

Abstract: Face recognition performance has improved remarkably in the last decade. Much of this success can be attributed to the development of deep learning techniques such as convolutional neural networks (CNNs). While CNNs have pushed the state-of-the-art forward, their training process requires a large amount of clean and correctly labelled training data. If a CNN is intended to tolerate facial pose, then we face an important question: should this training data be diverse in its pose distribution, or should face ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 51 publications
0
37
0
Order By: Relevance
“…Domain adaptation tools help to move or transfer knowledge between different domains. In the specific case of face recognition, face-frontalisation methods (methods that convert any face to its frontal view, allowing us to eliminate the pose bias) [24][25][26] represent a way of domain adaptation to work just with frontal faces. Since we could define a domain like the one that represents a certain dataset, it is easy to understand how these approaches help us to deal with the problem.…”
Section: Nature Of Dataset Biasmentioning
confidence: 99%
“…Domain adaptation tools help to move or transfer knowledge between different domains. In the specific case of face recognition, face-frontalisation methods (methods that convert any face to its frontal view, allowing us to eliminate the pose bias) [24][25][26] represent a way of domain adaptation to work just with frontal faces. Since we could define a domain like the one that represents a certain dataset, it is easy to understand how these approaches help us to deal with the problem.…”
Section: Nature Of Dataset Biasmentioning
confidence: 99%
“…reported a 1% recognition accuracy improvement on the LFW dataset when alignment was adopted in the testing stage [19]. It has also been shown that in terms of the recognition accuracy, 3D frontalization does not show significant improvements over simple 2D alignments [1]. Therefore, we will focus on the 2D image alignment only in this paper.…”
Section: Related Workmentioning
confidence: 99%
“…Suppose that for the i th target point p t i = (x t i , y t i , 1) in the output image, a grid generator generates its source coordinates (x s i , y s i , 1) in the input image according to transformation parameters. For the projective transformation, such a process can be expressed by (1) in which A to H are eight transformation parameters and z s i = Gx t i + Hy t i + 1.…”
Section: Spatial Transformer Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…This frontalization process is also called pose normalization. AbS methods can be categorised as a) 3D methods (AbS-3D) [18], [19], [20], [21], [22], [23], [24], [25], [26] and b) 2D methods (AbS-2D) [27], [28], [29], [30], [31]. AbS-3D methods fit a 3D model, typically a 3D Morphable Model (3DMM) [32], to an input face image with arbitrary pose.…”
Section: Introductionmentioning
confidence: 99%